Early introduction of an inert diet and unenriched Artemia enhances growth and quality of Atlantic cod (Gadus morhua) larvae. (11th March 2017) - Hansen, Ø.J.; Puvanendran, V.; Jøstensen, J.P.; Falk‐Petersen, I.‐B.
Abstract: The effects of two weaning diets and different weaning protocols on growth, survival, skeletal deformity and gut morphology of Atlantic cod larvae were studied in four groups from 16 to 45 days posthatch (dph). Cod larvae in groups 1 (early weaning with control diet) and 2 (early weaning with experimental diet) were used to evaluate the effects of different polar lipid content of weaning diets on larval and juvenile performance. Cod larvae in groups 2, 3 (early weaning with experimental diet + cofeeding with Artemia ) and 4 (earlier weaning with experimental diet and earlier cofeeding with Artemia ) were used to evaluate the effects of early introduction of dry diet and Artemia . From 45 to 170 dph, cod juveniles from all four groups were reared using a standard feeding protocol. No significant differences in growth, survival, deformities and gut morphology were found between cod larvae and juveniles from groups 1 and 2. Cod larvae fed on cofeeding regime with Artemia nauplii (groups 3 and 4) were bigger and had lower frequencies of jaw and neck deformities and higher foregut microvillus circumference than cod larvae from group 2. Our results demonstrate the importance of proper weaning protocols in producing better quality cod juveniles.